Socialization for OPD Admins of Sultan Muda Sumsel Super Apps: Improving OPD Admin Competence in Website Application Management - Rahman, M Arief; Ahmad Ari Gunawan Sepriansyah; Sony Oktapriandi; Ambar Sehatiningsih; Jason Gunawan; Zareena; Fairuzza; Siti Farizah (STIKES Columbia Asia Medan, 2026)
The socialization of Sultan Muda Sumsel Super Apps for OPD administrators was conducted to improve the capacity of administrators in managing website-based application content, data, and service information. The activity responded to the need for coordinated digital governance in supporting the 100,000 Sultan Muda program and the development of young entrepreneurship services in South Sumatra. The method consisted of need identification, material preparation, socialization, direct practice, and evaluation through discussion and technical assistance. The results show that the activity strengthened administrators’ understanding of application objectives, content management procedures, data accuracy, and follow-up mechanisms for digital publication. Documentation of the activity also reflects active mentoring, practical simulation, and coordination among stakeholders. The implication of this activity is the importance of continuous capacity building for OPD administrators to ensure that public digital service platforms are informative, updated, and aligned with institutional objectives.